Traitor Tracing Schemes: a Review - Antonius Cahya Prihandoko (INFORMAL: Informatics Journal, 2018)
This paper provides a review on traitor tracing schemes that are developed to counter piracy strategies. The review starts with a formal definition of the traitor tracing schemes. The paper is then outlined based on two main strategies which may taken by digital content pirates. Mostly the pirates have strategy to make use leaked decryption key or leaked decrypted content. For each piracy strategy, we presents traitor tracing schemes that can be used to counter the piracy. We also analysis strength and weakness of each group of the schemes. At the end of this paper, we propose to combine some schemes for better protection.